Using Lecture Demonstrations to Visualize Biological Concepts - Kristin Polizzotto (American Society for Microbiology, 2015)
Teaching complex biology concepts successfully can be challenging. The use of visual demonstrations has been shown to aid in this process, so we describe here two lecture demonstrations that instructors can use in introductory biology and genetics classes, and that students can easily remember and repeat on their own. The demonstrations do not require expensive equipment and use either props, which the instructor can borrow from the students, or participation of volunteer students. These demonstrations facilitate learning by allowing the student to more actively engage in the process, as we have formally documented in a separate study. They are described in detail here with the hope that other instructors and their students will also find them helpful. Three other props demonstrations for DNA replication, protein structure and linkage can be found using the url: https://sites.google.com/site/tamarif26. The effectiveness of the five props demonstrations was assessed. The results from an IRB approved study, which complements the descriptions provided here, also appear in this issue.